Sergio salva el partido - Rodriguez, Edel; Lombana, Juan Pablo (New York : Scholastic, 2010)
Although Sergio the penguin loves to play soccer, he is very clumsy and uncoordinated and he practices day and night, hoping he can help his team win the big game against the Seagulls.
AD 460
Accelerated Reader
Keywords: Penguins -- Juvenile fiction; Soccer stories -- Juvenile literature; Clumsiness -- Juvenile fiction